Interleukin-34 and Disease Activity in Systemic Lupus Erythematosus Patients - Rizki Luly Ya Fatwa Pulungan; Ratna Akbari Ganie; Zuhrial Zubir (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Systemic Lupus Erythematosus (SLE) is characterized by exacerbation and remission, which needs close monitoring ofthe disease activity. Systemic lupus erythematosus disease activity can be determined by the SLE Disease Activity Index(SLEDAI) score. Evaluation of the disease activity is essential to be a guidance for treatment. Interleukin-34 (IL-34) is relatedto the pathogenesis of SLE. Serum IL-34 can be a candidate marker to evaluate SLE disease activity, and it is correlated withthe SLEDAI score. This study aimed to determine the correlation between IL-34 level and disease activity in SLE patientsbased on the SLEDAI (Mex-SLEDAI) score. An observational analytical study with a cross-sectional design was carried out insix months (June-November 2019) in 27 SLE patients in the Department of Internal Medicine, Faculty of Medicine, SumateraUtara University/Adam Malik General Hospital, Medan. Systemic lupus erythematosus disease activity was measured basedon the Mex-SLEDAI score. Serum and urine were collected to obtain the Mex-SLEDAI score and IL-34 level. IL-34 level wasmeasured in all subjects by using Enzyme-Linked Immunosorbent Assay (ELISA). Spearman correlation test was used todetermine the correlation between IL-34 level and disease activity in SLE patients based on the SLEDAI (Mex-SLEDAI) score.There was a significant correlation between IL-34 level and disease activity in SLE patients based on SLEDAI (Mex-SLEDAI)score (r=0.965, p < 0.001). Further studies were needed with a sample of SLE patients in a balanced proportion based ontheir disease activity to obtain representative IL-34 levels in SLE patients based on their disease activity.